Killing me softly : a novel - Jones, Sandie (Reese's book club., 2026)
"What do you do when love turns deadly? THE PERFECT COUPLE Charlie and Freya used to be the picture-perfect couple. Happy and in love, Freya enjoyed a rewarding job heading up a charity's fundraising efforts, and Charlie was fast becoming one-to-watch on the London culinary scene-if you couldn't be them, you wanted to be with them. A TERRIBLE TRAGEDY They had it all . . . until one night a devastating accident tears their lives apart, and they're awoken by police at their door, asking whether they are aware that their car had been involved in a hit and run. A BITTER FEUD Torn apart by accusations and guilt, the trust that Freya and Charlie once shared is shattered as they turn on each other, looking for someone to blame for the fallout. Told from both Freya and Charlie's perspectives, a cat and mouse game ensues, both of them desperate to have someone to point the finger at. But is it more important to be right, or to win? Can Freya stay one step ahead of the man who knows her best? Or will Charlie's stoic conviction to get what he wants be the death of her? Sandie Jones's next addictive novel is a wickedly twisty tale of obsession, and the deadly consequences of loving someone too much"-- Provided by publisher.